O-fucosylation of CPN20 by SPINDLY Derepresses Abscisic Acid Signaling During Seed Germination and Seedling Development - Liang, Lin; Wang, Qi; Song, Zihao; Wu, Yaxin; Liang, Qing; Wang, Qingsong; Yang, Jinli; Bi, Ying; Zhou, Wen; Fan, Liu-Min (Frontiers in Plant Science, 2021)
SPINDLY (SPY) is involved in some aspects of plant development. However, the nature of this protein as an O-fucosyltransferase was recently discovered. In this study, we show that ¬¬SPY interacts with CPN20 in yeast two-hybrid and split-luc assays, and the interactio¬¬¬n is promoted by ABA. CPN20 is a chloroplast-localized co-chaperonin that negatively regulates ABAR-mediated ABA signaling. By using ETD (Electron Transfer Dissociation)-MS/MS analysis, two O-fucosylation sites, e.g. 116th and 119th threonines, were detected in ectopically expressed CPN20 in mammalian cells and Arabidopsis. The O-fucosylation at both threonine residues was confirmed by in vitro peptide O-fucosylation assay. We further show that CPN20 accumulates in the chloroplast of spy mutants, suggesting that SPY negatively regulates CPN20 localization in the chloroplast. In vivo protein degradation assay along with CPN20 localization behavior suggest that import of CPN20 into the chloroplast is negatively regulated by SPY. Genetic analysis shows that ABA insensitive phenotypes of spy-3 in terms of seed germination and early seedling development are partially suppressed by the cpn20 mutation, suggesting that CPN20 resides downstream of SPY in this ABA signaling pathway, and that there may exist other pathways in parallel with CPN20. Collectively, above data support a notion that the O-fucosylation of CPN20 by SPY fine-tunes ABA signaling in Arabidopsis.